Beyond Inclusion: Cultivating a Critical Sense of Belonging through Community-Engaged Research - Linnea K. Beckett; Flora Lu; Sheeva Sabati (Social Sciences, 2022)
A broad body of literature outlines the interventions to support underrepresented and minoritized students’ inclusion and sense of belonging into university contexts. In this paper, we explore how two first-generation students of color articulate a critical sense of belonging through their reflections as student researchers in the Apprenticeship in Community-Engaged Research or (H)ACER program at the University of California, Santa Cruz (UCSC). (H)ACER integrates community engagement, ethnographic sensibilities, critical race and decolonial theory, as well as women of color feminisms into a curriculum designed to train critical scholar-researchers. Through themes of feeling isolated on campus and returning ‘home’ in the garden, building comfort with academic theory, and navigating insider/outsider identities in campus/community contexts, we trace how the students developed an awareness of their positionality and made sense of their experiences of ‘belonging’, both within the campus and community contexts. Their narratives spark our deeper exploration into how critical approaches to community-engaged research may offer a pedagogy for supporting student sense of belonging that extends beyond inclusion, a promising vein of further research.